Doll bones - Black, Holly (Margaret K. McElderry Books, 2015)
Zach, Alice, and Poppy, friends from a Pennsylvania middle school who have long enjoyed acting out imaginary adventures with dolls and action figures, embark on a real-life quest to Ohio to bury a doll made from the ashes of a dead girl.